Pseudogenization of the cntQ permease confers distinct yersinopine-metal uptake selectivity in Yersinia species - Clémentine Laffont; Elizabeth Pradel; Laurent Ouerdane; Amélie Dewitte; Nicolas Oswaldo Gomez; Mathilde Tribout; Catherine Brutesco; Romé Voulhoux; Ryszard Lobinski; Florent Sebbane; Pascal Arnoux (BioMetals, 2026)
Yersinopine, a nicotianamine-like metallophore, was recently identified through biochemical analyses, but its in vivo production and functional role remain uncharacterized. In Yersinia pseudotuberculosis and its recent descendant Yersinia pestis , the cnt operon ( cntPQRLMI ) putatively encodes the biosynthesis and transport of yersinopine. In Y. pestis , however, two frameshift mutations disrupt cntQ , which encodes the predicted permease for yersinopine-metal complexes. This pseudogenization raises critical questions about the functional relevance of yersinopine in these closely related species. Here, we show that cnt operon expression is repressed by the zinc uptake regulator Zur and that both Y. pestis and Y. pseudotuberculosis secrete yersinopine under zinc-limited conditions. Unexpectedly, the operon mediates iron uptake in Y. pseudotuberculosis but supports zinc acquisition in Y. pestis . Moreover, targeted disruption of cntQ in Y. pseudotuberculosis shifts metal specificity from iron to zinc, mimicking the Y. pestis phenotype. Collectively, our results suggest that a single pseudogenization event could rewire metal uptake specificity. Our findings illustrate how evolutionary genome reduction can reshape bacterial physiology.

What do we know about osmoadaptation of Yersinia pestis? - Sébastien Bontemps-Gallo; Jean-Marie Lacroix; Florent Sebbane (Archives of Microbiology, 2022)